SPECIFIC ISSUES REGARDING THE EVALUATION OF REAL ESTATE SUBJECT TO EXPROPRIATION FOR THE CAUSE OF PUBLIC UTILITY - Tanasă, Florentin-Emil; Nuță, Florian Marcel (Revista de Studii Financiare, 2024)
In the last 20 years, the road infrastructure in Romania has expanded considerably and affected a significant number of natural and legal persons, owners of real estate located on the expropriation corridor. According to the Rejust database, in the last 10 years, annually, on average, approximately 4,000 files were created before the courts with expropriation as their object. In this article, we propose to present the legislative framework and particularities of the evaluation process of real estate properties subject to expropriation for reasons of public utility. The importance and actuality of such a theme was generated by the very large number of cases pending before the courts as a result of the dissatisfaction of the owners of buildings subject to expropriation for public utility reasons regarding the amount of compensation values granted. Also, at the level of the courts, there is a non-uniform practice regarding the method of drawing up evaluation reports. The study aims to review the procedures related to public interest expropriation and to create the premises for future research in the field.